2018
DOI: 10.7717/peerj.4713
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungal communities associated with field-grown soybean roots and seeds in the Huang-Huai region of China

Abstract: Plants depend on beneficial interactions between roots and fungal endophytes for growth, disease suppression, and stress tolerance. In this study, we characterized the endophytic fungal communities associated with the roots and corresponding seeds of soybeans grown in the Huang-Huai region of China. For the roots, we identified 105 and 50 genera by culture-independent and culture-dependent (CD) methods, respectively, and isolated 136 fungal strains (20 genera) from the CD samples. Compared with the 52 soybean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
1
22
0
4
Order By: Relevance
“…Prior studies have also shown, however, that fungal endophytes can be more abundant and diverse in plant tissues other than roots 39,40 . The reason for this discrepancy might be that the distribution of fungal endophytes across different tissue types is affected by different plant species, growth stages, soil types, and environmental conditions 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have also shown, however, that fungal endophytes can be more abundant and diverse in plant tissues other than roots 39,40 . The reason for this discrepancy might be that the distribution of fungal endophytes across different tissue types is affected by different plant species, growth stages, soil types, and environmental conditions 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In the past, only a few studies on seed-derived bacteria were published, because they are difficult to cultivate, while seed-borne archaea were not identified at all so far [10, 11]. Our knowledge related to seed fungi is much broader as reviewed by Geisen et al [12] and Yang et al [13], especially in terms of information available on clavicipitaceous endophytes such as Epichloë/Neotyphodium species due to their beneficial and specific interaction with grasses, which is already commercially exploited [14, 15]. However, we still need a complete picture of the seed microbiota and its interactions and functions in the holobiont.…”
Section: Introductionmentioning
confidence: 99%
“…Исследования эндофитной микобиоты здорового растения, основанные на этом подходе, также подтверждают значительное присутствие грибов рода Alternaria (13). В то же время подобный анализ с применением высокопроизводительного секвенирования показывает малую долю патогена в сообществе (0,35 %) (14), а в филлосфере ослабленного растения, пораженного грибом Podosphaera, -более значительную (0,35-4,6 %). Эти данные демонстрируют преимущества метагеномного подхода в исследованиях подобного рода.…”
Section: доля патогенов в сообществах грибов и грибоподобных организмunclassified
“…Альтернариоз и фитофтороз распространены во всех картофелеводческих регионах, проблемой борьбы с ними занимаются ученые в России и за рубежом. В частности, известны исследования филлопланы (3,12), эндофитных (13,14) и почвенных грибных сообществ (15,16), а также непосредственно участков растений, пораженных микозами (17,18); в результате были обнаружены возбудители фитофтороза, альтернариоза и других микологических заболеваний. Активно изучается воздействие на патогены различных агротехнических методов (15) и фунгицидов (8,10,19), которые могут использоваться в комбинации с другими средствами борьбы (20), например совместно с культуральной жидкостью бактерии Klebsiella planticola (21).…”
unclassified